Epigenetic regulation in neural crest development - Hu, Na (2014)
The neural crest is a migratory and multipotent cell population that plays a crucial role in many aspects of embryonic development. In all vertebrate embryos, these cells emerge from the dorsal neural tube then migrate long distances to different regions of the body, where they contribute to formation of many cell types and structures. These include much of the peripheral nervous system, craniofacial skeleton, smooth muscle, and pigmentation of the skin. The best-studied regulatory events guiding neural crest development are mediated by transcription factors and signaling molecules. In recent years, however, growing evidence supports an important role for epigenetic regulation as an additional mechanism for controlling the timing and level of gene expression at different stages of neural crest development. Here, we summarize the process of neural crest formation, with focus on the role of epigenetic regulation in neural crest specification, migration, and differentiation as well as in neural crest related birth defects and diseases.